Storytelling Magic: Enhancing EFL Learning for Kids - Ilahi, Witri Nur; azzahra, syeha nabila; Ilzamudin, Ilzamudin; Oktaviana, Fadilla (LPPM Universitas Pekalongan, 2024)
Effective communication is essential for all interaction, negotiations, and idea expression in daily life. As a result, by focusing on communicative skills like speaking especially speaking English we can enhance our language abilities. Worldwide, practically every region uses English as a language. One of the disciplines that needs to be learned is English. Many children or young learners have memory in thinking so when they train to speak, especially in learning English, they are quite capable in that Speaking and interacting in English is another advantage when seeking for a job. Many children or young learners have memory in thinking so when they train to speak, especially in learning English, they are quite capable in that regard. Sometimes the factor to train speaking in children is by way of storytelling. Story telling is quite adequate in learning English, especially in the aspect of speaking. Most children are very fond of stories such as fairy tales and folklore. Thus, being able to communicate in English will facilitate our ability to meet our wants and realize our objectives. Teachers can use the storytelling learning paradigm to help students become better public speakers. Students' speaking abilities can be enhanced by telling stories. Course institutions can also use storytelling as a means of enhancing students' ELF abilities. The aim of this study is to ascertain how using the Story Telling learning paradigm in classes affects students' ability to speak English more fluently. Using literature review approaches, such as examining and summarizing relevant publications, this research employs literature studies to gather data from numerous sources of connected journals and books. The study's findings demonstrated that using the Story Telling learning paradigm improved participants' ability to speak English.Keywords: Speaking abilities, ELF, and storytelling learning model, kids, Public SpeakingreferencesKylene, B., & Heinemann, B. (2009). When Kids Can ’ t Read : What Teachers Can Do Chapter 1 : Introduction Chapter 2 : Understanding Struggling Readers. Idea.